KELIMPAHAN BAKTERI PENDEGRADASI MINYAK BUMI DI PT. INDUSTRI KAPAL INDONESIA (Persero) MAKASSAR Makassar - Isnada Sulaiman (Jurnal Pendidikan Teknologi Pertanian, 2022)
This research is a descriptive study that aims to determine the abundance of marine bacteria at PT. Indonesian Ship Industry (Persero) in degrading petroleum. Water samples were taken from the territorial waters of PT. Indonesian Ship Industry (Persero) Makassar, with sampling points of 1 to 45.7 meters. Then diluted from 10-1 to 10-4, each dilution (10-1-10-4) was inoculated on a minimal solid medium using the pour cup method, the cup was incubated at 28ºC-30ºC for 48 hours. The data obtained are then analyzed using the Standard Plate Count (SPC) formula and then followed by observations of colonies in the form of colonies, color elevations, and internal structure. The results showed that the difference in bacterial abundance at the sampling point of 1 meter to 45.7 meters was the decrease in bacterial abundance from, taking point 3.6 meters to 45.7 meters while the observation of colonies took the form of edge elevation, color and structure in the colony. The results showed that there were colonies which were round, curly, filamentous, and irregular with convex and convex elevations, jagged edges, wavy, and even with a rough and smooth texture. The inner structure is clear, blurred and slippery and has a yellow and white color.